Mental health in times of pandemic from the perspective of professors and students - Campos, Juliana Alvares Duarte Bonini; Campos, Lucas Arrais; Azevedo, Maria Antonia Ramos; Martins, Bianca Gonzalez; Silva, Bianca Núbia Souza; Marôco, João (Frontiers in Education, 2024)
Introduction The COVID-19 pandemic brought profound societal changes and disruptions, including in the education system, which underwent swift modifications. It presented unique challenges for both professors and students, contributing to an increase in the prevalence of mental health-related symptoms. Objective To determine the prevalence of mental health disorders symptoms, coping strategies, and concerns among students (≥18 years) and professors at different times during the COVID-19 pandemic. Methods This was an online cross-sectional study (Student: N = 6,609; Phase 1 = 3,325; Phase 2 = 1,402; Phase 3 = 1,882; Professor: N = 9,096; Phase 1 = 3,924; Phase 2 = 2,223; Phase 3 = 2,949). Depression, Anxiety, and Stress Scale (DASS-21), Impact of Event Scale-revised (IES-R), and BriefCOPE inventory were used. The probability of presenting the symptoms was calculated by multiple logistic regression and odds ratio (OR). Results The prevalence of depression, anxiety, stress, and distress symptoms among students and professors was high (≥59.5% and ≥ 33.5%, respectively). Students, women, and those diagnosed with a mental disorder were more likely to have symptoms or distress. In the face of the pandemic, professors used more adaptive coping strategies than students. Health was the focus of professors’ concerns, while for students, future and labor market uncertainty were concerns derived from the health core. Conclusion The results point to the need to strengthen psychosocial support for both professors and students.